Plague epidemics in the southern region of the Habsburg Monarchy in XVIII century - fear, prejudices and consequences - Stojsavljević Rastislav; Gavrilović Darko; Ninković Nenad; Marković Vladimir; Kobilarov Aleksandar; Stamenković Igor (Vojnosanitetski Pregled)
nema